Propuesta metodológica para la Exportación y el Marco Tributario de la producción vinícola en la provincia de San Martín - Pinedo Nolorbe, Aldo (2003)
The procedure of the commercialization of the regional wine has been practicing for 40 years at regional as web as national level, but in the last few years the noncommercial export has been practiced much more which has motivated our interest to respond the question: Do a methodology and a tributary frame exist for the export of the wine in the province of San Martín and what the knowledge of this is? This with the purpose of knowing and applying it, this way to propose viable alternatives in order to improve the economic situation on the sanmartinense citizen. In the methodological aspects of the investigation work, the universe and sample are stated for being useful in this investigation, as well as the type, level and instruments applied in this work, that in this case are : questionnaire and bibliographical analysis. In the prosecution, analysis and interpretation of the results, the results of the investigation instruments are presented, reaching the contrast of the hypothesis and objectives which positively solve the problem exposition. Finally to conclude that it is necessary to raise a methodological proposal for the export of the wine. We hope the present descriptive work will be complemented by other works of greater depth, since to export our products will contribute to the socioeconomic development in our region.